A new technique waiting to improve in the diagnosis of breast cancer: Contrast-enhanced mammography - Sanli, Deniz Esin Tekcan; Yildirim, Duzgun (BAYRAKOL MEDICAL PUBLISHER, 2022)
The contrast-enhanced mammography technique, which was developed to reduce the false negativity and false positivity rates of full-field mammography, especially in dense breasts, and received FDA approval in 2011, has not been fully recognized even in the area of radiology. Based on this deficiency, this article aimed to give brief information about the advantages and disadvantages of contrast-enhanced mammography compared to digital mammography and breast magnetic resonance imaging, imaging technique, indications, and patient selection.
Keywords: Breast Cancer; Contrast-Enhanced Mammography; Dense Breast